1990
DOI: 10.1007/bf01332382
|View full text |Cite
|
Sign up to set email alerts
|

Small deformation viscoelastic response of gum and highly filled elastomers

Abstract: Small deformation viscoelastic response has been investigated in a series of five elastomeric binders, both with and without nonreinforcing filler. The filled system were found nonlinear viscoelastic and thermorheologically complex. These behavior suggest the existence of a secondary relaxation process. The origin of this secondary process was modeled as an interphase of polymer weakly adsorbed on the filler surface. Decomposition of time-temperature shift factors for filled vs unfilled properties showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…There is not a superposition of E ′ data at the lowest temperatures and highest frequencies for the HTPB1 propellant. This feature indicates a thermorheological complexity of the material under study, as previously observed in similar highly filled composite solid propellants 25, 26. Such thermorheological complex behavior is probably caused by the variation of the strength of filler–filler and filler–matrix interactions with temperature.…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…There is not a superposition of E ′ data at the lowest temperatures and highest frequencies for the HTPB1 propellant. This feature indicates a thermorheological complexity of the material under study, as previously observed in similar highly filled composite solid propellants 25, 26. Such thermorheological complex behavior is probably caused by the variation of the strength of filler–filler and filler–matrix interactions with temperature.…”
Section: Resultssupporting
confidence: 94%
“…The temperature location of this relaxation is shifted to higher temperatures in the composite as a result of the mobility reduction caused by filler incorporation. Temperature shifts ranging from 3 to 8°C are common in similar systems 26…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…HTPB‐based propellants show no simple thermo‐rheological behavior 5–7 due to the presence of secondary relaxation phenomena appearing at higher temperature. Each investigated AV0x formulation shows two apparent maxima.…”
Section: Resultsmentioning
confidence: 99%